The following description of the vascular flora of the Mesters Vig district, Kong Oscars Fjord, Northeast Greenland, is based mainly upon collections made in the summers of 1956 to 1958 inclusive, and 1960. It includes 154c species, and covers a land area - Washburn, A. L. (Meddelelser om Grønland, 1965)
The following description of the vascular flora of the Mesters Vig district, Kong Oscars Fjord, Northeast Greenland, is based mainly upon collections made in the summers of 1956 to 1958 inclusive, and 1960. It includes 154c species, and covers a land area of about 110 square kilometers. The flora is written with primary attention to the local behavior of the species in relation to habitat, to lifeform, and to geographic distribution. An attempt is made to rate each species in terms of its capacity to live at various levels on each of three habitat gradients: moisture, degree of coverage of the ground by vascular plants, and physical disturbance of the soil. Judgments are made on a presence or absence basis. Observations on the habitat preferences of each species made by earlier students of the Northeast Greenland flora are summarized and compared with those made at Mesters Vig. RAUNKIÆR's Life-form classification is used. The world distribution of each species is summarized, and also its general distribution in the Greenland coastal areas.